2022
DOI: 10.3389/fcell.2022.819044
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of N6-Methyladenosine-RNA in Mammalian Gametogenesis and Embryonic Development

Abstract: Emerging evidence shows that m6A is the most abundant modification in eukaryotic RNA molecules. It has only recently been found that this epigenetic modification plays an important role in many physiological and pathological processes, such as cell fate commitment, immune response, obesity, tumorigenesis, and relevant for the present review, gametogenesis. Notably the RNA metabolism process mediated by m6A is controlled and regulated by a series of proteins termed writers, readers and erasers that are highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 101 publications
1
11
0
Order By: Relevance
“…Previous studies reported that downregulation of m6A writer METTL3 and reader IGF2BP1 and YTHDF2 impaired early embryo development (Deng et al, 2020; Hao et al, 2020; Ivanova et al, 2017; Xia et al, 2018). Moreover, knockout of METTL3 or knockdown of IGF2BP1 reduced the m6A modification level (Chang et al, 2022; Hao et al, 2020). In addition, YBX1 interacts with IGF2BPs and stabilizes m6A‐tagged RNA (Feng et al, 2021) and IGF2BP1 is highly correlated with YBX1 (Deng et al, 2022), suggesting that YBX1 may be related to m6A.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that downregulation of m6A writer METTL3 and reader IGF2BP1 and YTHDF2 impaired early embryo development (Deng et al, 2020; Hao et al, 2020; Ivanova et al, 2017; Xia et al, 2018). Moreover, knockout of METTL3 or knockdown of IGF2BP1 reduced the m6A modification level (Chang et al, 2022; Hao et al, 2020). In addition, YBX1 interacts with IGF2BPs and stabilizes m6A‐tagged RNA (Feng et al, 2021) and IGF2BP1 is highly correlated with YBX1 (Deng et al, 2022), suggesting that YBX1 may be related to m6A.…”
Section: Discussionmentioning
confidence: 99%
“…[49] Recent studies have shown that YTHDF2 is required for the development of spermatogonia. [20][21][22][23] The inhibition of the G2 phase in GC-1 cells was caused by Ythdf2 depletion. Furthermore, YTHDF2 modulated cell-matrix adhesion mainly by regulating matrix metallopeptidase (MMPs) and extracellular matrix (ECMs) expression, and matrix metallopeptidase 13 (Mmp13) is an important target for YTHDF2 to regulate the phenotype.…”
Section: A Modification Regulated Spermatogonia Differentiationmentioning
confidence: 99%
“…Recent studies have summarized the role of m 6 A in spermatogenesis. [19][20][21][22][23] However, the mechanism by which m 6 A catalase enzymes contribute to specific germ cell stages remains unknown. Single-cell sequencing (scRNA-seq) techniques allow us to visualize the expression profile of m 6 A catalase enzymes in different germ cells.…”
Section: Introductionmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) acts as the most abundant posttranscriptional modification for mRNAs, which partially determines the fate of RNA, including RNA stabilization, splicing, and nuclear export [ 9 , 10 ]. m 6 A methylations have been shown to regulate series of inflammatory processes, including the inflammatory vascular disorder of endothelial cells in AS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%